Femininity of Japanese culture in Kawakami's Breasts and Eggs - Isnaeni Della Safitri; Sri Sumaryani (Universitas Negeri Semarang, 2025)
In Japanese society, women are expected to exhibit femininity shaped by the ideology of “good wife, wise mother” prevalent in Japan. This societal norm often limits women’s ability to pursue independent lives. However, the rise of the feminist movement has contributed to greater self-awareness among women, encouraging them to assert their rights and express their femininity in a non-traditional way. This study aims to explore how femininity is portrayed through female characters in Kawakami’s Breasts and Eggs. A descriptive qualitative method is employed in this research, drawing on Judith Butler’s theory of gender performativity. The results of this study suggest that femininity can be conveyed through the behavior, appearance, and language of several female characters, including Natsuko, Makiko, Midoriko, and Natsuko’s friend. The femininity portrayed by these characters also demonstrates that they both maintain and challenge traditional Japanese femininity. This depiction illustrates that femininity is constructed by society, which aligns with what Judith Butler discussed about gender.